The Problem Faced by PBG Students in the Third Semester in Listening Skill at Universitas Ma'arif Nahdlatul Ulama - Asroriyah, Atik Muhimatun; Wijayanto, Rori; Firharmawan, Hastri; Heriyanto, Dwi (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
English is a very important language nowadays, therefore many people learn english just to get a job and so on. learning english is very complex because english consists of four skills, namely speaking, writing, reading, and listening. listening skill is the most difficult skill compared to other skills because we need to understand what other people are saying. understanding sentences spoken by native speakers is a fairly complicated problem experienced by people learning a second language, especially for third semester students at universitas ma'arif nahdlatul ulama. the purpose of this study, to formulate the problems faced by PBG third semester students at universitas ma'arif nahdlatul ulama in learning listening comprehension. second, formulate the factors that affect difficulties in learning listening comprehension. third, formulate ways to overcome these problems. The study's findings show that the students had difficulties with the following: (1) they had trouble understanding the main idea and supporting details; (2) they lacked vocabulary; (3) they showed less initiative when reading; (4) they had trouble understanding the speaker's accent; (5) they lost focus; and (6) they had less desire to communicate